2012
DOI: 10.1111/j.1600-0846.2012.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aging effects on chemical property of human hair by Fourier transform infrared spectroscopy

Abstract: The changes in chemical components of the hair according to the ages were shown at the inflection point at 30 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Under the extension stress, Caucasian hair cuticles collapse to form small fragments while Asian hair cuticles fail as large pieces . When the keratin fibers are treated by chemical process, such as stretching, waving, and bleaching, the crosslinking of disulfide bond can be weakened or destroyed and caused the transformation of α‐helix→β‐pleated sheet . Meanwhile, the disulfide bond is oxidized into new cystine oxidation .…”
mentioning
confidence: 99%
“…Under the extension stress, Caucasian hair cuticles collapse to form small fragments while Asian hair cuticles fail as large pieces . When the keratin fibers are treated by chemical process, such as stretching, waving, and bleaching, the crosslinking of disulfide bond can be weakened or destroyed and caused the transformation of α‐helix→β‐pleated sheet . Meanwhile, the disulfide bond is oxidized into new cystine oxidation .…”
mentioning
confidence: 99%
“…The peaks at ∼1515 cm −1 and ∼1635 cm −1 correspond to the amide II and amide I region, respectively. 40 Due to these spectral differences, the synthetic hair spectrum can be visually differentiated from spectra of natural hair quite easily and, therefore, no advanced statistical modeling was necessary.
Figure 1.The raw mean spectra of synthetic, human, cat, and dog hair samples.
…”
Section: Resultsmentioning
confidence: 99%
“…The prominent features of an IR spectrum of natural hair correspond to specific vibrational modes of the amino acids and lipids present. 39 The averaged raw spectra for human, cat, dog, and synthetic hair, as shown in Figure 1, reveal visual differences between natural hair and synthetic hair spectra. These spectral differences include the absence of the amide A peak at 3300 cm À1 and the more intense CH 3 / CH 2 (alkane stretching) peak at 2950 cm À1 in the averaged synthetic hair fiber spectrum.…”
Section: Natural Hair Versus Synthetic Hairmentioning
confidence: 98%
“…This is because the untreated fibers hair showed only the band around 1235 cm ‐1 related to β‐sheet. In this way, it can be suggested that this last conformation dominated the structure of the cuticle and it was shown to be less ordered, that is, amorphous, as opposed to the underlying cortex; Increase in the band intensity around 803 cm ‐1 which is related to out‐of‐plane deformation in NH 2 . According to Mujeeb & Zafar, from 800 until 600 cm ‐1 related to cis–double bond (=CH), N–H wagging, CO 2 absorption and SO24- ions and NH 2.…”
Section: Discussionmentioning
confidence: 98%
“…This is because the untreated fibers hair showed only the band around 1235 cm -1 related to β-sheet. In this way, it can be suggested that this last conformation dominated the structure of the cuticle and it was shown to be less ordered, that is, amorphous, as opposed to the underlying cortex 23…”
Section: Discussionmentioning
confidence: 99%